Art Medium and Art Infrastructure Development in Contemporary Indonesian Art - A. Rikrik Kusmara (Journal of Visual Art and Design, 2013)
This research review Indonesian contemporary artists that used the various media in the presentation in his works over the years since 2000 until now. Survey at Pameran Besar Indonesia "Manifesto" in May 2008, were around 670 Indonesian living artists, 350 are consistently professional artists, 41 artists who utilize a variety of media in each works and 6 of them are artists who used a various of media on their solo exhibition including combining conventional media with new media and installation approaches. 6 artists are analyzed on the structure of the media presentation configuration their used, and generally they used more than 3 types of media in their solo exhibition, first, painting/drawing, second, sculpture/object/installation, and third video/photography. In the study of each exhibition process, generally utilizing the curatorial and sponsored by promotor (gallery). This research shows a rapid development of economic infrastructure in Indonesian the art in 2000-an era with the emergence of many auction hall, a new generation of collectors and galleries, and the Asian art market and global orientation, it became one of the holding in contemporary art of Indonesia, has been shifting art situation from cultural appreciation in the era of 90-to an era to cultural production.